PERANCANGAN MASTER PLAN KEBUN EDUWISATA BENDOSARI DENGAN MERESPON KEADAAN ALAM - Eulis Yulianti Faridah (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2021)
The very noble vision of the managers of the Bendosari orchard, to turn the Bendosari orchard into an edutourism garden, initiated UIN Sunan Kalijaga Yogyakarta to offer cooperation in realizing this great vision. The vision aims to make Bendosari fruit orchards for producing and developing knowledge, which can then become a field laboratory in the context of research and community service. Departing from this, the purpose of this research is to design a master plan for the Bendosari Edutourism Garden in accordance with the knowledge possessed by the author, namely the field of architecture. In architecture, some of the characteristics of edutourism facilities and services are protecting the surrounding environment, both in the form of the natural environment and local culture, having minimal impact on the natural environment during the construction and operation period, according to the cultural and physical context of the local area. Based on this, the design that responds to nature is very important in the process of designing an edutourism area. The methodology used is a descriptive method, starting with the preparation stage, with data collection through interviews to determine the assessment of user requests and data collection in the form of literature review, then proceed with survey/inventory and observation stages to be able to conduct site analysis, finally making a master plan design. The results of this study are in the form of a master plan design for the Bendosari edutourism garden area which is designed according to the natural conditions at the site location, taking into account the conditions of the direction of sunlight, wind speed and direction, topography, and the direction of water flow.